La qualité de l’environnement physique et interactif de classes de maternelle 4 ans à temps plein en milieu défavorisé : regard sur la place octroyée aux livres et à la lecture au sein de six classes - Beaudry, Hélène; Charron, Annie (Canadian Journal of Education/Revue canadienne de l'éducation, 2025)
The quality of the educational environment in the classroom is recognized as paramount in supporting the emergence of writing in preschool children (Guo et al., 2012). The aim of this descriptive qualitative research is to paint a portrait of the quality of the educational environment in its physical and interactive dimensions with regard to books and book reading in full-time preschool classes in disadvantaged areas of Quebec, the educational environment of which is generally of good quality. Six classes were selected from a larger sample of 30 classes, for which the quality of educational environment had been assessed for a larger study. To assess this quality, the ELLCO Pre-K observation tool (Smith et al., 2008) was used, notably to collect qualitative data from: (1) note-taking for the “Books and Book Reading” domain, (2) classroom photographs, and (3) semi-structured interviews conducted with teachers. A conceptual categorical analysis of the qualitative data relating to books and book reading identified strengths, such as the frequency of interactive readings led by teachers, and challenges, such as the quantity of books available in the reading corner.